Green Synthesis Nanopartikel Perak (Agnps) Terkonjugasi Etil Parametoksi Sinamat (Epms) sebagai Bahan Tabir Surya - Agustina Agustina; Munawarah Munawarah; Stefanus Agustinus Lumi; Syamsu Nur (Universitas Tadulako, 2018)
Green Synthesis is a method to make silver nanoparticles (AgNPs) by utilizing natural materials as bioreductors. One of the natural materials that can reduce metal ions is Kaempferia galanga rhizome because it has a chemical component that can penetrate the metal. The compounds are ethyl paramethoxycinnamate (EPMC) which is used as sunscreen. This study aims to produce AgNPs conjugated with EPMC that can be used as raw material sunscreen. This study was conducted by extracting EPMS from the Kaempferia galanga rhizome and synthesizing the AgNPs conjugated with EPMC. The synthesis results were characterized by UV-Vis Spectrophotometry, FTIR, SEM, PSA and sunscreen activity. Extracted result was obtained crystalline is ethyl paramethoxycinnamate compound with yield 2,3%. The characterization of EPMC with UV-Vis spectrophotometer was obtained maximum wavelength of 308 nm and FTIR analysis result at wave number 1701,27 cm-1 indicated the presence of carbonyl group (C = O) and 1165,97 cm-1 presence of C-O and showed specific characteristic from EPMS. Characterization of AgNPs using Uv-Vis spectrophotometer was obtained maximum wavelength of 469 nm. Characterization of AgNPs using SEM are spherical and monodispers forms.  Then, particle size using PSA obtained an average diameter of 182 nm. AgNPs conjugated with EPMS has a sunscreen activity with sunblock category and successfully provide protection against UV exposure at low concentration (200 ppm) categorized as ultra protection with SPF value 36,4.